Improving Students’ Vocabulary Mastery By Using Flash Card At Forth Grade Students In SDN Lawangan Daya 2 Pamekasan - Arisandi Setiyawan (Universitas Islam Madura, 2015)
From the preliminary research of the fourth graders of SDN Lawangan Daya 2 Pamekasan, it showed that most of the students had a lack of vocabulary mastery. This research is conducted to find an effective and appropriate strategy to improve students‟ vocabulary mastery by using flashcard. Therefore, the appropriate design for this research is Classroom Action Research (CAR). The researcher implemented the strategy in one cycle, those are: planning, implementing, observing and reflecting. The result of the class vocabulay test is analyzed quantitatively, while the result of the data achieved from observation class is analyzed qualitatively. The finding shows that the students‟ vocabulary mastery increase significantly from the preliminary research. The result can be concluded that (1) teaching and learning process needs an appropriate and effecctive strategy, (2) flashcard is considered as an appropriate technique to improve the students‟ vocabulary mastery.